The French Army and its African soldiers : the years of decolonization - Ginio, Ruth, 1966- (France overseas., 2016)
"An examination of the role of the French Army in French West Africa and its relations with its African soldiers from the end of World War II to the final demobilization of African troops from the French Army in 1964"--Provided by publisher